Global distributions of capital and labor incomes: Capitalization of the global middle class - Marco Ranaldi (Luxembourg Income Study (LIS), 2021)
This article studies global distributions of capital and labor income among individuals in 2000 and 2016. By constructing a novel database covering approximately the 80% of the global output and the 60% of the world population, two major findings stand out. First, the world underwent a spectacular process of capitalization. The share of world individuals with positive capital income rose from 20% to 32%. Second, the global middle class benefited the most, in relative terms, from such capitalization process. In China, the average growth rate of capital income was 20 times higher than in western economies. The global composition of capital and labor income is, therefore, more equal today than it was twenty years ago, and the world is moving towards a global multiple-sources-of-income society.
Keywords: D31; 330; Global Inequality; Capital and Labor; Compositional Inequality